Über die Grenzverteilungen von multiplikativen zahlentheoretischen Funktionen (III) - Bakštys, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бакштис. О предельных законах распределения мультипликативных арифметических функций (III) A. Bakštys. Multiplikatyvinių aritmetinių funkcijų ribinių pasiskirstymo dėsnių klausimu (III)